Sisters of Perpetual Indulgence at the San Jose train depot. - Sahl, Ted (photographer):::Creator::::::::::::
Sisters of Perpetual Indulgence in full nun costume at the San Jose train depot. Photograph shows the sisters stopping to pose for photograph while on their way to the San Jose's Freedom Day Rally.